PENERAPAN INTEGRASI LITERASI VISUAL UNTUK MENINGKATKAN PEMAHAMAN TEKS SISWA KELAS VI DI SDN MANNURUKI (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the text comprehension of sixth-grade students at SDN Mannuruki through the implementation of visual literacy integration in Indonesian language learning. The background of this research is based on the low level of students’ text comprehension, as indicated by their difficulties in identifying main ideas, finding important information, and drawing conclusions from reading texts. This study employed Classroom Action Research (CAR) conducted in two cycles, consisting of planning, action, observation, and reflection stages. The subjects of this research were 25 sixth-grade students of SDN Mannuruki. Data were collected through observation, tests, and documentation. The action implemented was the integration of reading texts with visual media such as images to support students in understanding the content more effectively. The results showed that the implementation of visual literacy integration improved students’ text comprehension. This improvement was indicated by the increase in learning mastery from 24% in the first cycle to 72% in the second cycle . In addition, students’ participation, interest, and engagement in the learning process also increased. In conclusion, the integration of visual literacy is effective in improving the text comprehension of sixth-grade students at SDN Mannuruki.